Kudus Regional Regulation Number 10 of 2015 Concerning Discotheque, Night Club, PUB, and Karaoke Entertainment Arrangement Businesses - Irsyad Santoso; Vicki Dwi Purnomo; Syukron Abdul Kadir; Benedictus Hestu Cipto Handoyo (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
The Regional Regulation of Kudus Regency, Kudus Regency Number 10 of 2015, in its implementation, has not been fully successful in implementing and realizing the principles of good governance. The approach method used in this study is sociological juridical with primary data and secondary data. The research results obtained are that the implementation of the Kudus Regency Regional Regulation of Kudus Regency Number 10 of 2015 concerning Discotheque Entertainment Business, Night Clubs, PUB, and Arrangement of Karaoke Entertainment is full of discriminatory actions considering that not all people in Kudus Regency are Muslim. In addition, the Kudus Regency Regional Regulation Number 10 of 2015 does not contain the principle of equality and participation. Implementation of the Regional Regulation, the local government has carried out outreach and warnings both verbally and in writing, the Regional Government has also carried out raids and even forced closure of business actors who are still determined to operate. At present the government continues to supervise so that the entertainment venues no longer operate.